Microscopic and macroscopic investigation on the gas diffusion in poly(ether-block-amide) membranes doped with polysorbate nonionic surfactants. (17th November 2020) - Simari, Cataldo; Nicotera, Isabella; Perrotta, Ida Daniela; Clarizia, Gabriele; Bernardo, Paola
Abstract: Gas transport properties through nanocomposite membranes incorporating nonionic surfactants (polysorbates) in a poly (ether- block -amide), Pebax®1657, were investigated by two complementary techniques: the time-lag method in a manometric apparatus to analyze the permeation process of CO2 and CH4, and the 1 H and 13 C NMR spectroscopy to study the molecular dynamics by the direct measurements of the self-diffusion coefficients (Pulsed Field Gradient-PFG technique) and spectral analysis. The diffusion coefficients of CO2 and CH4 gas molecules measured by microscopic and macroscopic techniques are in agreement, provided that the gas pressure is opportunely set. NMR allows a deeper study of the molecular dynamics and confinement effects, revealing dual pathways within the nanocomposite membranes that result in different self-diffusion for the bulkier CH4 molecules. Morphological and thermal analyses proved the effect of the polysorbate incorporation on the microstructure of the nanocomposite films: lowered glass transition temperature of the polymer polyether block and reduced crystallinity of the Pebax blocks, additional endothermic peak and presence of 'micellar-like' domains. Graphical abstract: Image 1 Highlights: Gas diffusion in Pebax nanocomposite membranes incorporating nonionic surfactants. Time-lag method and multinuclear PFG-NMR to study the gas molecular dynamics. Polysorbates modify the film's microstructure with micellar domains. Dual diffusive pathways for CH4 molecules in the nanocomposite membranes emerged.